(untitled) (Journal of Health, Population and Nutrition, 2013)
Studies on twin pregnancy are uniquely important to Africa and particularly Nigeria where the highest incidence in the world exists. This study was designed to determine the trend, rate, and obstetric outcomes of twin deliveries in the University of Abuja Teaching Hospital, Gwagwalada. This was a retrospective study of twin deliveries in the hospital over a period of 10 years. During the study period, there were 349 twin births out of 10,739 deliveries, giving an overall twining rate of 32.5 per 1,000 deliveries. Preterm delivery occurred in 39.7% cases and was, therefore, the most common complication. Mode of delivery was vaginal in 72.7% while 27.3% were delivered by caesarean section. Emergency caesarean section for delivery of both the babies was carried out in 22.3% while elective caesarean section for both the babies accounted for 1.0 %. Combined vaginal and abdominal delivery occurred in 4.0% of deliveries. The stillbirth rate was 102 per 1,000 births. There were 24 (8.0%) and 37 (12.3%) stillbirths among the first and the second baby respectively. The mean foetal weight was 2.395±0.63 kg while the female-to-male ratio was 1:1.1. The rate of twin deliveries in our centre is high. Successful vaginal delivery of twins is high when the mothers are booked and the presentations of the twins are favourable. The use of antenatal care services and good intrapartum management will help improve outcome in twin pregnancies. J HEALTH POPUL NUTR 2013 Jun; 31(2): 272-277 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16392